2020
DOI: 10.3846/btp.2020.10850
|View full text |Cite
|
Sign up to set email alerts
|

Risk Governance and Financial Performance: An Empirical Analysis

Abstract: This study examines the influence of risk governance on financial performance of 50 quoted firms in the Nigerian financial sector for the period of five years (2013–2017). Panel data was used to examine how the risk governance variables (Enterprise Risk Management_index, Chief Risk Officer_presence, Board Risk Committee_size, Board Risk Committee_activism, and Board Risk Committee_independence) affects financial performance (Return on Asset). The study reveals empirically that most of the risk governance varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…Moreover, previous studies showed how accounting scholars could favor the diffusion of these new paradigms with practitioners (Hopper, 2019; Olayinka et al. , 2019; Erin et al. , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, previous studies showed how accounting scholars could favor the diffusion of these new paradigms with practitioners (Hopper, 2019; Olayinka et al. , 2019; Erin et al. , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Second, value provision: accountants are expected to inform and guide managerial and operational decision-making alongside the implementation of strategies set for value creation. They are also expected to plan, monitor and improve supporting processes (Erin et al , 2020). Third, value keeping: accountants are expected to ensure the protection of sustainable value creation strategy against strategic, operational and financial risk and also to ensure compliance with regulations, good practices and standard and finally, value reporting: accountants are expected to enable transparent communication of delivery of sustainable value to stakeholders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The NSBP is a guideline on sustainability reporting peculiar to the Nigerian financial service sector to improve sustainability practice and disclosure by Nigerian banks. The motivation for the issuance of the NSBP stems from the observation that Nigerian banks are doing little to practice and report on sustainability (Oyewo and Isa, 2017; Erin et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%